ROLE MODEL FOR EDUCATORS AS AN ALTERNATIVE IN THE ESTABLISHMENT OF ISLAMIC CHARACTER - Samsul Arifin; Eva Maghfiroh (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2022)
The role of educators in Islamic religious education (PAI) is very important for the formation of the character of students in madrasas. Therefore, an educator must be able to set a good example. Educators are role models for their students. Strengthening character in the context of education is an important factor in the ongoing part of the education system. This relates to the direct interaction of educators with their students, where students will see, hear and feel directly what is taught by educators, following the philosophy of the educators themselves, which is defined as someone who is